Myocardial Infarction in the Neonate Without Coronary Artery Occlusion and Structurally Normal Heart: A Report of 2 Cases in Twin Pregnancies and Review of the Literature. (December 2019) - Sathirareuangchai, Sakda; Placek, Alexander L; Killeen, Jeffrey L; Thompson, Karen S
Myocardial infarction (MI) is a common diagnosis in the adult population and is associated with coronary artery atherosclerosis. However, it is an unusual diagnosis in the pediatric population, especially in the neonatal period. The authors present 2 autopsy cases of MI in newborn babies of twin pregnancies with normal heart and coronary arteries. The first case is that of a 10-day-old female, monochorionic-diamniotic, twin B born at 29 weeks' gestation. The autopsy revealed diffuse subacute MI in both ventricles, which was compatible with a global hypoxic event during perinatal period. The hypoxic insult was likely caused by maternal HELLP (hemolysis, elevated liver enzymes, low platelet count) syndrome as evident in the placental examination, which showed placental infarct and decidual arteriopathy. The second case is that of a 2-day-old term male, dichorionic-diamniotic, twin A with an antenatal history of prolonged rupture of membranes. The hospital course was complicated by neonatal sepsis. The autopsy showed diffuse hemorrhage in the internal organs including the heart, along with myocyte necrosis. The overall findings were consistent with multiorgan dysfunction syndrome resulting from sepsis. Previous reported cases of MI in neonates without coronary artery occlusion were also reviewed and portrayed.